Experiences of female partners of prostate cancer survivors: A systematic review and thematic synthesis. (10th November 2021) - Green, Anna; Winter, Natalie; DiGiacomo, Michelle; Oliffe, John L.; Ralph, Nicholas; Dunn, Jeff; Chambers, Suzanne K.
Abstract: The purpose of this systematic review and synthesis of studies reporting qualitative data was to understand the gendered experiences of female partners of prostate cancer survivors to inform psychosocial support for women. We searched Medline, PsycINFO, EMBASE, AMED, CINAHL, Cochrane Database of Systematic Reviews, and Sociological Abstracts for articles on 15 and 16 April 2019, and again on 30 November 2020. English language articles published in peer‐reviewed journals were included if they reported solely on findings describing the perspectives of the female partners. Extracted data were analysed using line‐by‐line coding, organisation of codes into descriptive themes, and development of analytical themes. A theoretical framework was then selected to organise the relationships between issues that were found to be central to the experiences of female partners. Of 4839 articles screened, 14 met inclusion criteria, reporting 13 studies with a total sample of 359 female partners. Ussher and Sandoval's theory to describe the gendered positionings of cancer caregivers accommodated the thematic findings. The overarching theme reflected the substantive psychosocial impact of prostate cancer on female partners. Women's experiences were influenced by self‐positioning (as part of a couple; provider of support to their male partner; resilient; and guided by faith and spirituality), being positioned by their partners' response (manager of male partner's psychological distress or strengthened by male partner's positive response) and by their broader contexts (family members and social networks; clinicians and the health system; and cultural values and customs). Findings highlight the need to avoid reductionist approaches to gender. Greater consideration of 'contextualised femininities', or conceptualising the influence of gender roles, relations, and identities within the wider life course contexts of female partners is required in the design and delivery of psychosocial support services.